2008
DOI: 10.1016/j.jaapos.2008.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Results of ocular dominance testing depend on assessment method

Abstract: Results of ocular dominance tests vary depending on both the testing distance and the specific activity performed as part of the testing procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 16 publications
4
48
1
1
Order By: Relevance
“…The optimum method to evaluate ocular dominance is controversial. A recent report by Rice and colleagues 19 has shown that results may vary depending on the test used to identify ocular dominance. We chose to adopt the hole-in-card test at 50 cm and 5 m because it is one of the simplest and most commonly used tests in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…The optimum method to evaluate ocular dominance is controversial. A recent report by Rice and colleagues 19 has shown that results may vary depending on the test used to identify ocular dominance. We chose to adopt the hole-in-card test at 50 cm and 5 m because it is one of the simplest and most commonly used tests in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…By and large these methods have proven rather unreliable (e.g. Banks, Ghose & Hillis, 2004, Khan & Crawford, 2001), and they tend to be unrelated to one another and/or to other binocular visual functions (Ehrenstein, Arnold-Schulz-Gahmen & Jaschinski, 2005, Mapp, Ono & Barbeito, 2003, Pointer, 2007, Rice, Leske, Smestad & Holmes, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…There is a high correlation among the scores from these three tests, and the preference for one eye over the other in these tests is consistent and has excellent test-retest reliability [17,25]. In addition, there is a considerable consistency between the dominant eye according to the positioning tests mentioned previously and the eye that is used in more conscious sighting tasks, such as sighting with a rifle or looking through a microscope [9].…”
Section: Discussionmentioning
confidence: 99%